Questioning library neutrality : essays from Progressive librarian - Lewis, Alison M., 1959- (Library Juice Press, 2008)
Questioning Library Neutrality: Essays from Progressive Librarian presents essays that relate to neutrality in librarianship in a philosophical or practical sense, and sometimes both. They are a selection of essays originally published in Progressive Librarian, the journal of the Progressive Librarians Guild, presented in the chronological order of their appearance there.